Pengaruh Locus Of Control, Professional Commitment, Dimoderasi Time Budget Pressure Terhadap Underreporting Time - Kevin, Hendro Lukman (Jurnal Paradigma Akuntansi, 2019)
The purpose of this research is to examine the influence of internal locus of control, external locus of control, and professional commitmen towards acceptance of underreporting of chargeable time with time budget pressureas moderator in external auditors who works at Public Accounting Firms in Jakarta. The sample was determined by convenience sampling and snowball sampling method. The research conducted with printed questionnaires and online questionnaires. The result of this research shows that internal locus of control, external locus of control, and professional commitment have no significant effect partially and simultaneously towards acceptance of underreporting of chargeable time. However, those three independent variables have positive significant effect towards dependent variable when moderated by time budget pressure